Leptospirosis in free-living capybaras (Hydrochaeris hydrochaeris) from a university campus in the city of Araras in São Paulo, Brazil - Gonçalves, Daniela Dib; Cardoso Lopes, Karoline Franciane; Chiderolli, Roberta Torres; Sampieri, Bruno Rodrigues [UNESP]; Rocha, Vlamir José; Pachaly, José Ricardo; Dos Santos, Isabela Carvalho; Barbosa, Lidiane Nunes; Mota, Edinalva Almeida; De Pádua Pereira, Ulisses (Universidade Estadual de Londrina, 2020)
The capybara (Hydrochaeris hydrochaeris L. 1766) is the largest existing rodent in the world. This animal species, being synanthropic, may serve as a transmitter of different diseases and parasitic infections in animals and humans as well. Leptospirosis is a cosmopolitan infectious disease with a high prevalence in tropical and subtropical regions that can affect humans and other domestic and wild animals. Due to the absence of regional data and the importance of this animal species in transmitting diseases to animals and humans, the aim of this study was to analyze DNA and anti-Leptospira spp. antibodies in free-living capybaras (Hydrochaeris hydrochaeris) from a university campus in the city of Araras in São Paulo, Brazil. A total of 31 capybaras (Hydrochaeris hydrochaeris) were captured for collecting their blood samples. The collected sera were analyzed using the microscopic agglutination test (MAT). For the detection of Leptospira spp. DNA, the serum samples were used to extract genomic DNA for the nested-PCR analysis. Out of the 31 serum samples, 29 (93.55%) were reactive for MAT, with titers ranging from 25 to 400. The antibody could be identified against the most probable serovar in 26 (89.65%) samples, namely: Grippotyphosa (69.23%), Autumnalis (26.92%), and Bratislava (3.85%). Presence of Leptospira via nested-PCR was found only in 3.22% of serum samples. This study revealed the presence of DNA and anti-Leptospira spp. antibodies in free-living capybara. Characterization of these animals as possible carriers and disseminators of the etiological agent in the environment is necessary for identification of infection in other animals and campus visitors.
Keywords: Antibodies; Grippotyphosa; Hydrichaeridae; Leptospira spp; Molecular Biology; Zoonosis